Evaluation of a Vibrotactile Biofeedback System Targeting Stance Time Symmetry Ratio of Individuals With Lower-Limb Amputation: A Pilot Study - R. Escamilla-Nunez; A. Gouda; J. Andrysek (IEEE, 2023)
Individuals with lower-limb amputation (LLA) often exhibit atypical gait patterns and asymmetries. These patterns can be corrected using biofeedback (BFB). Real-time BFB strategies have demonstrated to be effective to various degrees in BFB systems. However, no studies have evaluated the use of corrective vibrotactile BFB strategies to improve temporal gait symmetry of LLA. The aim of this study was to evaluate a wearable vibrotactile BFB system to improve stance time symmetry ratio (STSR) of LLA, and compare two corrective BFB strategies that activate either one or two vibrating motors at two different frequency and amplitude levels, based on a pre-set STSR target. Gait patterns of five unilateral LLA were assessed with and without BFB. Spatiotemporal and kinematic gait parameters were measured and assessed using a wearable motion capture system. Usability and workload were assessed using the System Usability Scale and NASA Task Load Index questionnaires, respectively. Results showed that participants significantly ( $\text{p}< 0.001$ ) improved STSR with BFB; however, this coincided with a reduction in gait speed and cadence compared to walking without feedback. Knee and hip flexion angles improved and changes in other parameters were variable. Immediate post-test retention effects were observed, suggesting that gait changes due to BFB were preserved for at least a short-time after feedback was withdrawn. System usability was found to be acceptable while using BFB. The outcomes of this study provide new insights into the development and implementation of clinically practical and viable BFB system. Future work should focus on assessing the long-term use and retention effects of BFB outside controlled-laboratory conditions.